Reflections on “Geography and Religions” - WOODS, Orlando (Institutional Knowledge at Singapore Management University, 2024)
David E. Sopher’s (Prog Human Geogr 5(4):510–524, 1981) landmark essay marks a turning point in geographical scholarship on religion. Published as the cultural turn was gaining momentum in human geography, Sopher calls out the fact that much geographical work on religion had been hitherto preoccupied with the themes of denominational dynamics, spatial distributions of religion across space and landscape, and the role of sacred centers and pilgrimage routes in determining patterns of religious mobility. In his call for a broadening and deepening of geographical scholarship on religion, he paved the way for the emergence of the so-called “new” geographies of religion that emerged in the early 1990s. Notwithstanding, Sopher’s call for geographers to study the “neglected questions” of how religion intersects with ecology have been largely ignored until very recently, thus providing an indication of the prescience of a paper that was published more than four decades ago. This reflection contextualizes Sopher’s work, offering insight into the genesis of his ideas, the importance of the cultural turn in shaping his thinking, and an appreciation of how he paved the way for much of the contemporaneous geographical scholarship on religion.